2011
DOI: 10.3892/ijo.2011.1220
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells promote tumor engraftment and metastatic colonization in rat osteosarcoma model

Abstract: Abstract.Although mesenchymal stem cells (MSCs) are considered to be the cells of origin for most sarcomas, the role of MSCs as a source of tumor stroma is not fully understood in this tumor type. The current study investigated whether MSCs affect the tumor growth and metastatic ability in rat osteosarcoma model. Results from subcutaneous co-implantation of rat osteosarcoma COS1NR cells, established in our laboratory, with rat MSCs isolated from femur bone marrow showed that the incidence of tumor formation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…Exogenous MSCs could target the OS site and promote OS growth and progression in a mouse xenograft model [122]. Similar results were also found in a rat model [123]. IL-6 secreted by MSCs could activate STAT3 signaling in OS cells, which in turn augment cell proliferation, migration, invasion, and pulmonary metastasis [124].…”
Section: Stromal Niche: Bone Marrow Mesenchymal Stem Cellsupporting
confidence: 58%
“…Exogenous MSCs could target the OS site and promote OS growth and progression in a mouse xenograft model [122]. Similar results were also found in a rat model [123]. IL-6 secreted by MSCs could activate STAT3 signaling in OS cells, which in turn augment cell proliferation, migration, invasion, and pulmonary metastasis [124].…”
Section: Stromal Niche: Bone Marrow Mesenchymal Stem Cellsupporting
confidence: 58%
“…In addition, a study showed that B16 melanoma cells transplanted into allogeneic mice did not form tumors unless co-injected with MSCs (8). Subcutaneous inoculation of COS1NR cells followed by intravenous injection of MSCs at weeks 3 and 5 significantly increased the number of lung nodules (9). It has also been demonstrated that MSCs enhance the survival of follicular lymphoma B cells derived from human tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is extremely useful for cancer stem cell research of bone tumors, where orthotopic injections of small number of cancer cells are required to demonstrate tumor initiating potential of cellular populations having stem-like properties, since establishment of tumors is dependent on the number of tumor initiating cells within cells transplanted [24]. Furthermore, several reports demonstrate that co-injection of human cancer cells with human stromal cells enhances tumor growth, suggesting the significance of proper tumor microenvironment [8, 25]. It would be interesting to compare tumor growth between injection of human osteosarcoma cells alone and co-injection of osteosarcoma cells with human stromal cells, using our established model as a future study.…”
Section: Discussionmentioning
confidence: 99%